Optimizing Shoulder Joint Positioning During Video‐Assisted Thoracoscopic Surgery: A Prospective Study on Prevention of Postoperative Ipsilateral Shoulder Pain - Yan Zhao; Yang Gu; Bin Hu (Thoracic Cancer)
ABSTRACT Background Ipsilateral shoulder pain (ISP) is a common complication following video‐assisted thoracoscopic surgery (VATS), significantly affecting postoperative recovery and quality of life. This study aimed to evaluate the relationship between intraoperative upper limb positioning, and the occurrence of ISP, with the goal of optimizing positioning to reduce postoperative complications. Methods This prospective cohort study included 252 patients undergoing VATS for lung resection. The A angle (shoulder flexion) and B angle (shoulder abduction) were measured intraoperatively. ISP was assessed using the Visual Analog Scale (VAS) on the first postoperative day and 1 week after surgery. Univariate and multivariate logistic regression analyses were performed to identify predictors of ISP, and receiver operating characteristic (ROC) curve analysis was used to evaluate the diagnostic accuracy of shoulder positioning in predicting ISP. Results The incidence of ISP was 26.2% (66/252). Multivariate analysis revealed that larger A angles (OR: 1.061, 95% CI: 1.009–1.115, p = 0.021) were associated with a higher risk of ISP, while larger B angles (OR: 0.798, 95% CI: 0.744–0.856, p < 0.001) were protective against ISP. ROC curve analysis demonstrated a strong predictive value for the combined influence of A and B angles, with an area under the curve (AUC) of 0.822. Conclusion Intraoperative upper limb positioning, specifically decreasing the A angle (shoulder flexion) and increasing the B angle (shoulder abduction), plays a critical role in reducing the incidence of ISP following VATS. These findings suggest that adopting an optimal shoulder posture during surgery can improve patient outcomes.